Surgical site infections post-ventriculoperitoneal shunting: A matched healthcare cost and length of stay study: Empirical research quantitative - Issa M. Hweidi; Saba W. Al-Ibraheem; Omar H. Jebreel (Heliyon)
Aim: To assess the increased hospital length of stay and healthcare costs associated with SSIs among ventriculoperitoneal shunting surgery patients in Jordan. Design: Retrospective and nested 1:1 pair-matched case-control design. Methods: A non-probability convenience sample of 48 VP shunt patients was recruited into SSI and non-SSI groups, to standardize the matching variables and exclude their effects as confounders. Data sources: Patients’ electronic medical records from January 2016 to August 2021. Results: The SSI-group had an extra mean healthcare cost of USD 13,696.53 and a longer hospital length of stay (22.64 mean additional days). Furthermore, Acinetobacter baumanii and Klebsiella pneumonia were identified as being the most predominant causative agents of SSIs. Conclusion: The results of this study provide baseline data for national and regional benchmarking to evaluate the quality of care provided to likewise patients. Adherence to infection control strategies and protocols considering new surveillance methods of SSIs are encouraged. Implications for the profession and/or patient care: National benchmarking and remediation are required for post-VP shunting SSIs. Impact: There are significant associations of SSI post neurosurgery with increased financial burden and wastage of healthcare resources. The findings of this study can be utilized as a standard source for national benchmarking to evaluate the quality of care delivered to likewise patients and promote their infection control measures. Multidrug-resistant bacteria have recently been considered a growing concern for SSIs post-VP shunting. These impacts affect post-VP shunting patients and their healthcare professionals. Reporting method: EQUATOR's reporting guidelines for Observational studies (STOBE- Strengthening the Reporting of Observational Studies in Epidemiology) have been followed for this research design. Patient or public contribution: Patients’ EMRs were used to source data.